2009
DOI: 10.1182/blood-2008-02-137752
|View full text |Cite
|
Sign up to set email alerts
|

Potentiating effects of RAD001 (Everolimus) on vincristine therapy in childhood acute lymphoblastic leukemia

Abstract: Despite advances in the treatment of acute lymphoblastic leukemia (ALL), the majority of children who relapse still die of ALL. Therefore, the development of more potent but less toxic drugs for the treatment of ALL is imperative. We investigated the effects of the mammalian target of rapamycin inhibitor, RAD001 (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
89
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 48 publications
9
89
0
Order By: Relevance
“…[132] Since that initial report, the activity of a number of rapalogs, including everolimus, sirolimus, and temsirolimus have been extensively studied in ALL in preclinical models by our group and others, establishing activity not only in cell lines and transgenic mouse models, but also against primary human ALL samples supported in vitro with stromal cells and in vivo with immunodeficient mouse strains. [131,132,[134][135][136][137][138][139][140] Our work and the work of others suggest that rapalogs may have the highest degree of activity against ALL types with the worst prognosis, including pre-T, adult, BCR-ABL and Ikaros mutant. [29,135,141,142] Supporting this are recent data demonstrating that early engraftment of pre-B-ALL in immune-deficient mice is associated with the activation of the mTOR pathway and a very high risk of relapse.…”
Section: Acute Lymphoblastic Leukemiamentioning
confidence: 53%
See 1 more Smart Citation
“…[132] Since that initial report, the activity of a number of rapalogs, including everolimus, sirolimus, and temsirolimus have been extensively studied in ALL in preclinical models by our group and others, establishing activity not only in cell lines and transgenic mouse models, but also against primary human ALL samples supported in vitro with stromal cells and in vivo with immunodeficient mouse strains. [131,132,[134][135][136][137][138][139][140] Our work and the work of others suggest that rapalogs may have the highest degree of activity against ALL types with the worst prognosis, including pre-T, adult, BCR-ABL and Ikaros mutant. [29,135,141,142] Supporting this are recent data demonstrating that early engraftment of pre-B-ALL in immune-deficient mice is associated with the activation of the mTOR pathway and a very high risk of relapse.…”
Section: Acute Lymphoblastic Leukemiamentioning
confidence: 53%
“…[136,[144][145][146] An added benefit was not found when rapalogs were combined with vincristine in vitro; however, the combination was found to be more effective than either drug alone in vivo. [136,139,146] Rapalogs have been studied in vivo in combination with methotrexate and corticosteroids.…”
Section: Acute Lymphoblastic Leukemiamentioning
confidence: 99%
“…9 mTOR inhibitors have significant anti-tumor activity as single agents in vitro and in experimental mouse models of ALL. 6,[10][11][12][13] Furthermore, positive interactions have been demonstrated between mTOR inhibitors and standard chemotherapeutics including vincristine, doxorubicin and methotrexate, 3,[13][14][15] as well as newer growth factor receptor or tyrosine kinase inhibitors with anti-cancer agents targeting growth factor pathways. 16 Indeed we have demonstrated that the survival of mice receiving vincristine and RAD001 is enhanced, while Teachey et al found similar results with the combination of methotrexate and CCI-779.…”
Section: Introductionmentioning
confidence: 99%
“…The use of human ALL cells to engraft immune-deficient mice has been previously exploited to assess the effect of new drugs in the treatment of ALL 42,43 or even to predict the response of a specific patient to standard chemotherapy such as vincristine and dexamethasone. 44 However, our approach differs from those of previous studies as we have developed a model that can be transplanted into multiple generations of animals without significant changes either in their genetic or epigenetic makeup.…”
Section: In Vitro Activity Of Lbh589 In All Cellsmentioning
confidence: 99%